1995
DOI: 10.1128/mcb.15.3.1265
|View full text |Cite
|
Sign up to set email alerts
|

A Ubiquitin Mutant with Specific Defects in DNA Repair and Multiubiquitination

Abstract: The degradation of many proteins involves the sequential ligation of ubiquitin molecules to the substrate to form a multiubiquitin chain linked through Lys-48 of ubiquitin. To test for the existence of alternate forms of multiubiquitin chains, we examined the effects of individually substituting each of six other Lys residues in ubiquitin with Arg. Substitution of Lys-63 resulted in the disappearance of a family of abundant multiubiquitin-protein conjugates. The UbK63R mutants were not generally impaired in ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
415
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(431 citation statements)
references
References 58 publications
10
415
0
4
Order By: Relevance
“…The possible role of the UBC9 pathway in DNA repair has been suggested from studies of ubc9 mutants (21). Indeed, our results have also demonstrated that a ubc9 ts mutant is hypersensitive to hTOP1-mediated DNA damage induced by CPT (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The possible role of the UBC9 pathway in DNA repair has been suggested from studies of ubc9 mutants (21). Indeed, our results have also demonstrated that a ubc9 ts mutant is hypersensitive to hTOP1-mediated DNA damage induced by CPT (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…UBC9 was originally identified to play an essential function in G 2 -M cell cycle progression in yeast (20). However, UBC9 is also known to be important for DNA repair (21). It has been shown that SUMO-1 can be conjugated to a number of proteins such as PML (22), RanGAP1 (23,24), I B␣ (25), FAS͞apolipoprotein-1 (26), p53 (27,28), RAD51, and RAD52 (29).…”
mentioning
confidence: 99%
“…PolyUb chains assembled via Lys 29 have been implicated in degradation of certain model proteasome substrates (10). Lys 63 -linked polyUb chains, on the other hand, function in post-replicative DNA repair in the RAD6 pathway (11,12), I B␣ kinase activation (13), translational regulation (6), and some instances of endocytosis (14), although their mechanistic role in these processes is still unclear. Mono-Ub, like Lys 63 -linked polyUb chains, is not involved in proteasome proteolysis and appears to act as a trafficking signal in a host of processes, including endocytosis, endosome internalization, and viral budding (for reviews, see Refs.…”
mentioning
confidence: 99%
“…The preparation of ubiquitin-specific antibodies has been hampered by low affinity and high background, so the introduction of N-terminally epitope-tagged ubiquitin as a probe was quickly identified as a useful alternative for ubiquitination studies [74]. Tagged ubiquitin allows for a more robust purification [75], as it can be performed under strongly denaturing conditions [76]. Cells transformed with tagged-ubiquitin formed the basis for several studies in different organisms that have been undertaken since, with the first large-scale study performed in yeast [54].…”
Section: Using Epitope-tagged Ubiquitinmentioning
confidence: 99%